Numerical Exploratory of a Magneto Piezo Elastic Oscillator with Bouc-Wen Damping to Energy Harvesting - Ribeiro, Mauricio Ap; Tusset, Angelo M.; Lenz, Wagner Barth; Felix, Jorge L.P.; Litak, Grzegorz; Balthazar, Jose M. (AIP Publishing, 2022)
We investigated the mathematical model of a ferromagnetic cantilever beam containing patches of piezoceramic materials for vibration energy harvesting. The beam is coupled to a hysterical Bouc-Wen damper. One of the beam end is clamped to the vibrating frame. It contains the piezoelectric patch coupled to an electric circuit for energy transduction. The other end is attracted to two permanent magnets located on the left and right sides. Applied to the system a motor with an external force causing vibrations of the frame and, consequently, produces the inertial forces in the beam. In order to compare the behavior of the system's output power, and the nonlinear dynamic properties our analyzes were focused to variations of the external force frequency and changing the parametrization of the complex non-ideal excitation.
Keywords: Bouc-Wen damping; Energy harvesting; Nonlinear dynamics